High-toughness high-strength epoxy structural adhesive film and preparation method thereof
By introducing thermoplastic resins and functional toughening agents into epoxy structural adhesives and adopting hot pressing composite technology, the problem of high brittleness of epoxy structural adhesives is solved, and the combination of high toughness and high strength is achieved, which is suitable for high-demand bonding applications.
Patent Information
- Application Number
- CN202510070968.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
AI Technical Summary
The epoxy structural glue has a high brittleness after curing, making it difficult to have both high toughness and high strength, which limits its application range.
A high toughness and high strength epoxy structural adhesive film is prepared by hot press composite technology using a glue composed of epoxy resin, curing agent, thermoplastic resin, functional toughening agent and silane coupling agent.
It improves the toughness and strength of epoxy structural adhesives, while maintaining their adhesive properties and heat resistance, and is suitable for metal or composite adhesives in the aerospace field.
Smart Images

Figure CN119875556A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of epoxy structural adhesives, and specifically relates to a high-toughness and high-strength epoxy structural adhesive film and a preparation method thereof. Background Art
[0002] Adhesives are generally divided into structural adhesives and non-structural adhesives. The biggest feature of structural parts made of structural adhesives is light weight and high strength, which is an indispensable performance requirement for aircraft manufacturing. In addition, the bonded structure also has special functions such as crack resistance, wave absorption, shock absorption, heat insulation, and sound insulation, so it is widely used. At present, structural adhesives and bonding technology are applied to various structures and fields, and the amount of adhesives used is also increasing significantly. Structural adhesives have become an important material in industrial production.
[0003] Epoxy structural adhesive has the advantages of excellent bonding performance, light weight, low price, wide source of raw materials, simple bonding process, high corrosion resistance, good insulation performance, low curing volume shrinkage and easy processing and molding. At the same time, epoxy resin adhesive can be cured at different temperatures and in dry environment, humid environment and even in water. In recent years, it has been widely used in the fields of automobile, medical, water conservancy and transportation, electronic appliances and aerospace industry. However, the brittleness of epoxy structural adhesive after curing has hindered the application of epoxy structural adhesive. How to improve the toughness of epoxy structural adhesive has become the key to solving this problem. Common toughening methods of epoxy structural adhesive include thermoplastic resin toughening, inorganic nanoparticle toughening, rubber toughening, etc.
[0004] Currently, most epoxy structural adhesives are toughened and modified by a single-component toughening method. Single-component toughened epoxy structural adhesives with high strength generally have poor toughness, and high toughness but insufficient strength, making it difficult to combine multiple excellent properties. Therefore, it is of great significance to design an epoxy structural adhesive with high toughness and high strength. Summary of the invention
[0005] In order to solve the problem that epoxy structural adhesives are difficult to have both high toughness and high strength, the present invention provides a high-toughness and high-strength epoxy structural adhesive film and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A high-toughness and high-strength epoxy structural adhesive film, which is made by hot-pressing a rubber compound and a carrier for film manufacturing; the rubber compound comprises 75-100 parts of epoxy resin, 5-25 parts of curing agent, 20-60 parts of thermoplastic resin, 5-30 parts of functional toughening agent, and 3-5 parts of silane coupling agent, and the functional toughening agent comprises a combination of one or two of terminal epoxy-butadiene nitrile rubber and poly(glycidyl methacrylate) and core-shell rubber; when the functional toughening agent comprises terminal epoxy-butadiene nitrile rubber, poly(glycidyl methacrylate) and core-shell rubber, the weight ratio of the three is (1-2):(1-2):(1-5); when the functional toughening agent comprises terminal epoxy-butadiene nitrile rubber / poly(glycidyl methacrylate) and core-shell rubber, the weight ratio of the two is (1-2):(1-5).
[0008] Furthermore, the chemical structural formula of the epoxy-terminated nitrile rubber is as shown in Formula I:
[0009]
[0010] In the above structural formula, n is in the range of 10 to 20, m is in the range of 5 to 10, and a is in the range of 10 to 15;
[0011] The chemical structural formula of the poly(glycidyl methacrylate) is shown in Formula II:
[0012]
[0013] The value of x in the above structural formula ranges from 5 to 20.
[0014] The epoxy-terminated nitrile rubber is prepared by mixing vinyl-terminated nitrile rubber, glycidyl methacrylate and an initiator in a molar ratio of 1:(1.05-1.2):0.2, and reacting the mixture in an electric constant temperature blast drying oven at 110±5°C through free radical polymerization for 60±5 minutes; the poly(glycidyl methacrylate) is prepared by mixing glycidyl methacrylate and an initiator in a molar ratio of 1:0.2, and reacting the mixture in an electric constant temperature blast drying oven at 110±5°C through copolymerization for 70±5 minutes.
[0015] The epoxy resin is composed of bisphenol A diglycidyl ether epoxy resin, naphthyl epoxy resin and biphenyl phenol formaldehyde epoxy resin in a weight ratio of (1-4): (1-2): (1-2).
[0016] The curing agent is composed of 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenylmethane and dicyandiamide in a weight ratio of (1-2):(1-2):(1-5).
[0017] The thermoplastic resin includes any one or any several of polysulfone resin, phenolphthalein polyarylethersulfone, and phenolphthalein polyaryletherketone. When the thermoplastic resin is selected from polysulfone resin, phenolphthalein polyarylethersulfone, and phenolphthalein polyaryletherketone, the mass ratio of the three is 1:(0.25-1):(0.25-1); when the thermoplastic resin is selected from polysulfone resin and phenolphthalein polyarylethersulfone / phenolphthalein polyaryletherketone, the mass ratio of the two is 1:(0.25-1); when the thermoplastic resin is selected from phenolphthalein polyarylethersulfone and phenolphthalein polyaryletherketone, the mass ratio of the two is (0.25-1):(0.25-1).
[0018] The silane coupling agent includes any one or more combinations of γ-glycidyloxypropyltrimethoxysilane, 3-(3,4-epoxypropyl)propyltrimethoxysilane, and 3-(2,3-epoxypropyl)propyltrimethoxysilane.
[0019] The carrier for manufacturing the adhesive film includes one of non-woven fabric, carbon fiber woven fabric, polyester gauze, quartz fiber woven fabric or glass fiber woven fabric.
[0020] A method for preparing the high-toughness and high-strength epoxy structural adhesive film comprises the following steps:
[0021] Step 1: Add epoxy resin into a reaction kettle, heat to 200-220°C, add thermoplastic resin at one time under stirring, keep warm at 190-200°C for 80±5min, and prepare a homogeneous blended resin;
[0022] Step 2: uniformly mixing the homogeneous blended resin with the functional toughening agent, the curing agent and the silane coupling agent by mechanical blending to obtain a rubber compound;
[0023] Step 3: hot-press the prepared adhesive material and the carrier for film manufacturing to form a composite film, so as to obtain a high-toughness and high-strength epoxy structural adhesive film.
[0024] In step three, the hot pressing composite film forming temperature is 70-90°C.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The bisphenol A diglycidyl ether type epoxy resin used in the present invention is combined with a biphenyl phenolic type epoxy resin and a naphthyl epoxy resin to improve the temperature resistance and mechanical properties of the system. The amine and aromatic amine curing agent combination used is better compatible with the epoxy resin than the curing agent of a single component, and the curing latency of dicyandiamide is longer, which is beneficial to the preservation of the epoxy structural adhesive. The thermoplastic resin used is used as a toughening phase. When the epoxy structural adhesive is subjected to the action of a critical tensile force, the thermoplastic particles will cavitate, forming a cavitation area at the crack tip. At the same time, the cavitation induces the appearance of shear yield, which eventually stops the crack extension, thereby effectively improving the toughness of the epoxy structural adhesive. The functional toughening agent is used as the second toughening phase. The epoxy-terminated nitrile rubber and poly(glycidyl methacrylate) can form chemical crosslinks with the curing agent due to the presence of epoxy terminal groups, thereby resisting the slippage of the molecular chain under high temperature conditions and improving the mechanical properties of the system. The core-shell rubber particles are not affected by the curing reaction kinetics during the curing process, and their morphology, size, and composition do not change before and after curing, thereby reducing their influence on the modulus of the bonding system.
[0027] From the performance point of view, a high-toughness and high-strength epoxy structural adhesive film is prepared based on thermoplastic resin and second synergistic phase functional toughening agent. The toughness and strength of epoxy structural adhesive are improved by introducing epoxy groups, cyano groups, etc., and the bonding performance of epoxy structural adhesive is also greatly improved, and the heat resistance of epoxy structural adhesive is almost unaffected. The high-toughness and high-strength epoxy structural adhesive film of the present invention has excellent process performance, outstanding mechanical properties and bonding properties, and has the characteristics of high strength and high toughness. It meets the large-area bonding molding process of metal or composite materials, solves the demand for high-strength bonding of structural parts of aerospace vehicles, and is suitable for bonding of metal or composite structural parts in the aerospace field.
[0028] The high-toughness and high-strength epoxy structural adhesive prepared by the present invention is used for bonding aluminum alloy plates and continuous carbon fiber composite material plates. The tensile shear strength at room temperature is ≥40MPa, the bonding peel strength between aluminum alloy plates at room temperature is ≥6N / mm, and the impact strength is ≥60kJ / m 2 , glass transition temperature ≥190℃. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 , infrared spectrum of epoxy-terminated nitrile rubber.
[0030] Figure 2 , the structural formula of epoxy-terminated nitrile rubber.
[0031] Figure 3 , infrared spectrum of poly(glycidyl methacrylate).
[0032] Figure 4 , the structural formula of poly(glycidyl methacrylate).
[0033] Figure 5 , glass transition temperature curve of the epoxy structural adhesive in Example 3. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] A high-toughness and high-strength epoxy structural adhesive film is prepared by preparing an adhesive material from epoxy resin, a curing agent, a thermoplastic resin, a functional toughening agent and a silane coupling agent in the following weight proportions, and then the adhesive material is compounded with a carrier for film manufacturing by hot pressing:
[0037] The rubber material includes 75 parts of epoxy resin, 5 parts of curing agent, 20 parts of thermoplastic resin, 5 parts of functional toughening agent and 3 parts of silane coupling agent;
[0038] The epoxy resin is composed of bisphenol A diglycidyl ether epoxy resin, naphthyl epoxy resin, and biphenyl phenolic epoxy resin in a weight ratio of 3:1:1, namely, 45 parts of bisphenol A diglycidyl ether epoxy resin, 15 parts of naphthyl epoxy resin, and 15 parts of biphenyl phenolic epoxy resin.
[0039] The curing agent is composed of 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenylmethane and dicyandiamide in a weight ratio of 1:1:3, namely, 1 part of 4,4'-diaminodiphenyl sulfone, 1 part of 4,4'-diaminodiphenylmethane and 3 parts of dicyandiamide.
[0040] The thermoplastic resin is composed of polysulfone resin, phenolphthalein polyarylethersulfone and phenolphthalein polyaryletherketone in a weight ratio of 1:0.3:0.3, namely, 12.5 parts of polysulfone resin, 3.75 parts of phenolphthalein polyarylethersulfone and 3.75 parts of phenolphthalein polyaryletherketone.
[0041] The functional toughening agent is composed of core-shell rubber and epoxy-terminated nitrile rubber in a weight ratio of 1:1, that is, 2.5 parts of core-shell rubber and 2.5 parts of epoxy-terminated nitrile rubber.
[0042] The epoxy-terminated nitrile rubber is prepared by mixing vinyl-terminated nitrile rubber, glycidyl methacrylate and an initiator in a molar ratio of 1:1.05:0.2 and reacting the mixture in an electric constant temperature forced air drying oven at 110°C through free radical polymerization for 60 minutes.
[0043] The chemical structure of the epoxy-terminated nitrile rubber is shown in Formula I:
[0044]
[0045] In the above structural formula, the value of n is 10, the value of m is 5, and the value of a is 10.
[0046] The silane coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane, 3-(3,4-epoxypropyl)propyltrimethoxysilane and 3-(2,3-epoxypropyl)propyltrimethoxysilane in a weight ratio of 1:1:1, that is, 1 part of γ-glycidyloxypropyltrimethoxysilane, 1 part of 3-(3,4-epoxypropyl)propyltrimethoxysilane and 1 part of 3-(2,3-epoxypropyl)propyltrimethoxysilane.
[0047] The carrier used for making the film is a quartz fiber woven cloth with a specification of 80 mesh and a surface density of 25g / m 2 .
[0048] A method for preparing the high-toughness and high-strength epoxy structural adhesive film comprises the following steps:
[0049] (1) Weigh 45 parts of bisphenol A diglycidyl ether epoxy resin, 15 parts of naphthyl epoxy resin, 15 parts of biphenyl phenolic epoxy resin, 1 part of 4,4'-diaminodiphenyl sulfone, 1 part of 4,4'-diaminodiphenylmethane, 3 parts of dicyandiamide, 12.5 parts of polysulfone resin, 3.75 parts of phenolphthalein polyarylethersulfone, 3.75 parts of phenolphthalein polyaryletherketone, 2.5 parts of epoxy-terminated nitrile rubber, 2.5 parts of core-shell rubber, 1 part of γ-glycidyloxypropyltrimethoxysilane, 1 part of 3-(3,4-epoxypropyl)propyltrimethoxysilane, and 1 part of 3-(2,3-epoxypropyl)propyltrimethoxysilane respectively by weight;
[0050] (2) adding 45 parts of bisphenol A diglycidyl ether epoxy resin, 15 parts of naphthyl epoxy resin and 15 parts of biphenyl phenolic epoxy resin weighed in step (1) into a reaction kettle, heating to 200° C., adding 12.5 parts of polysulfone resin, 3.75 parts of phenolphthalein polyarylethersulfone and 3.75 parts of phenolphthalein polyaryletherketone at once under stirring, and keeping the temperature at 190° C. for 80 minutes to obtain a homogeneous blended resin;
[0051] (3) using a kneader, uniformly mixing the homogeneous blended resin obtained in step (2) with 1 part of 4,4'-diaminodiphenyl sulfone, 1 part of 4,4'-diaminodiphenylmethane, 3 parts of dicyandiamide, 2.5 parts of epoxy-terminated nitrile rubber, 2.5 parts of core-shell rubber, 1 part of γ-glycidyloxypropyl trimethoxysilane, 1 part of 3-(3,4-epoxypropyl)propyl trimethoxysilane, and 1 part of 3-(2,3-epoxypropyl)propyl trimethoxysilane to obtain a rubber material;
[0052] (4) hot-pressing the adhesive prepared in step (3) and the quartz fiber woven cloth to form a composite film to prepare an epoxy structural adhesive film;
[0053] The temperature of the hot pressing composite film forming is 70°C.
[0054] The high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is used for bonding aluminum alloy plates and continuous carbon fiber composite material plates. The tensile shear strength is shown in Table 1:
[0055]
[0056] The impact strength of the high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is 61.2 kJ / m 2 .
[0057] The high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is used for bonding aluminum alloy plates at room temperature, and the peel strength is 6.26 N / mm.
[0058] The glass transition temperature of the high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is 190.7°C.
[0059] Example 2
[0060] A high-toughness and high-strength epoxy structural adhesive film is prepared by preparing an adhesive material from epoxy resin, a curing agent, a thermoplastic resin, a functional toughening agent and a silane coupling agent in the following weight proportions, and then the adhesive material is compounded with a carrier for film manufacturing by hot pressing:
[0061] The rubber material includes 90 parts of epoxy resin, 15 parts of curing agent, 30 parts of thermoplastic resin, 15 parts of functional toughening agent and 3 parts of silane coupling agent;
[0062] The epoxy resin is composed of bisphenol A diglycidyl ether epoxy resin, naphthyl epoxy resin, and biphenyl phenolic epoxy resin in a weight ratio of 2:2:1, namely, 36 parts of bisphenol A diglycidyl ether epoxy resin, 36 parts of naphthyl epoxy resin, and 18 parts of biphenyl phenolic epoxy resin.
[0063] The curing agent is composed of 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenylmethane and dicyandiamide in a weight ratio of 1:1:3, namely 3 parts of 4,4'-diaminodiphenyl sulfone, 3 parts of 4,4'-diaminodiphenylmethane and 9 parts of dicyandiamide.
[0064] The thermoplastic resin is composed of polysulfone resin, phenolphthalein polyarylethersulfone and phenolphthalein polyaryletherketone in a weight ratio of 1:0.5:0.5, namely, 15 parts of polysulfone resin, 7.5 parts of phenolphthalein polyarylethersulfone and 7.5 parts of phenolphthalein polyaryletherketone.
[0065] The functional toughening agent is composed of core-shell rubber and epoxy-terminated liquid nitrile rubber in a weight ratio of 2:1, that is, 10 parts of core-shell rubber and 5 parts of epoxy-terminated nitrile rubber.
[0066] The epoxy-terminated nitrile rubber is prepared by mixing vinyl-terminated nitrile rubber, glycidyl methacrylate and an initiator in a molar ratio of 1:1.1:0.2 and reacting the mixture in an electric constant temperature forced air drying oven at 110°C through free radical polymerization for 65 minutes.
[0067] The chemical structure of the epoxy-terminated nitrile rubber is shown in Formula I:
[0068]
[0069] In the above structural formula, the value of n is 15, the value of m is 8, and the value of a is 12.
[0070] The silane coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane and 3-(3,4-epoxypropyl)propyltrimethoxysilane in a weight ratio of 1:1, that is, 1.5 parts of γ-glycidyloxypropyltrimethoxysilane and 1.5 parts of 3-(3,4-epoxypropyl)propyltrimethoxysilane.
[0071] The carrier used for making the film is a non-woven fabric with a specification of 80 mesh and a surface density of 25g / m 2 .
[0072] A method for preparing the high-toughness and high-strength epoxy structural adhesive film comprises the following steps:
[0073] (1) Weigh 36 parts of bisphenol A diglycidyl ether epoxy resin, 36 parts of naphthyl epoxy resin, 18 parts of biphenyl phenolic epoxy resin, 3 parts of 4,4'-diaminodiphenyl sulfone, 3 parts of 4,4'-diaminodiphenylmethane, 9 parts of dicyandiamide, 15 parts of polysulfone resin, 7.5 parts of phenolphthalein polyarylethersulfone, 7.5 parts of phenolphthalein polyaryletherketone, 10 parts of core-shell rubber, 5 parts of epoxy-terminated nitrile rubber, 1.5 parts of γ-glycidyloxypropyltrimethoxysilane, and 1.5 parts of 3-(3,4-epoxypropyl)propyltrimethoxysilane respectively by weight;
[0074] (2) Add 36 parts of bisphenol A diglycidyl ether epoxy resin, 36 parts of naphthyl epoxy resin, and 18 parts of biphenyl phenol formaldehyde epoxy resin weighed in step (1) into a reaction kettle, heat to 210° C., add 15 parts of polysulfone resin, 7.5 parts of phenolphthalein polyarylethersulfone, and 7.5 parts of cyclophenolphthalein polyaryletherketone at once under stirring, and keep warm at 195° C. for 85 minutes to obtain a homogeneous blended resin;
[0075] (3) using a kneader, uniformly mixing the homogeneous blended resin obtained in step (2) with 3 parts of 4,4'-diaminodiphenyl sulfone, 3 parts of 4,4'-diaminodiphenylmethane, 9 parts of dicyandiamide, 10 parts of core-shell rubber, 5 parts of epoxy-terminated nitrile rubber, 1.5 parts of γ-glycidyloxypropyltrimethoxysilane, and 1.5 parts of 3-(3,4-epoxypropyl)propyltrimethoxysilane to obtain a rubber material;
[0076] (4) hot-pressing the adhesive prepared in step (3) and the non-woven fabric to form a composite film to prepare an epoxy structural adhesive film;
[0077] The temperature of the hot pressing composite film forming is 80°C.
[0078] The high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is used for bonding aluminum alloy plates and for bonding continuous carbon fiber composite plates. The tensile shear strength is shown in Table 2:
[0079]
[0080] The impact strength of the high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is 61.6 kJ / m 2 .
[0081] The high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is used for bonding aluminum alloy plates at room temperature, and the peel strength is 6.30 N / mm.
[0082] The glass transition temperature of the high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is 190.6°C.
[0083] Example 3
[0084] A high-toughness and high-strength epoxy structural adhesive film is prepared by preparing an adhesive material from epoxy resin, a curing agent, a thermoplastic resin, a functional toughening agent and a silane coupling agent in the following weight proportions, and then the adhesive material is compounded with a carrier for film manufacturing by hot pressing:
[0085] The rubber material comprises 100 parts of epoxy resin, 20 parts of curing agent, 40 parts of thermoplastic resin, 10 parts of functional toughening agent and 4 parts of silane coupling agent;
[0086] The epoxy resin is composed of bisphenol A diglycidyl ether epoxy resin, naphthyl epoxy resin, and biphenyl phenolic epoxy resin in a weight ratio of 3:1:1, that is, 60 parts of bisphenol A diglycidyl ether epoxy resin, 20 parts of naphthyl epoxy resin, and 20 parts of biphenyl phenolic epoxy resin.
[0087] The curing agent is composed of 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenylmethane and dicyandiamide in a weight ratio of 1:2:5, namely 2.5 parts of 4,4'-diaminodiphenyl sulfone, 5 parts of 4,4'-diaminodiphenylmethane and 12.5 parts of dicyandiamide.
[0088] The thermoplastic resin is composed of polysulfone resin, phenolphthalein polyarylethersulfone and phenolphthalein polyaryletherketone in a weight ratio of 1:0.5:0.5, namely 20 parts of polysulfone resin, 10 parts of phenolphthalein polyarylethersulfone and 10 parts of phenolphthalein polyaryletherketone.
[0089] The functional toughening agent is composed of core-shell rubber and poly(glycidyl methacrylate) in a weight ratio of 1:1, that is, 5 parts of core-shell rubber and 5 parts of poly(glycidyl methacrylate).
[0090] Poly(glycidyl methacrylate) is prepared by mixing glycidyl methacrylate and an initiator in a molar ratio of 1:0.2 and subjecting the mixture to copolymerization in an electric constant temperature blast drying oven at 110°C for 70 minutes.
[0091] The chemical structure of poly(glycidyl methacrylate) is shown in Formula II:
[0092]
[0093] The value of x in the above structural formula is 10.
[0094] The silane coupling agent is composed of γ-glycidyloxypropyl trimethoxysilane, 3-(3,4-epoxypropyl)propyl trimethoxysilane and 3-(2,3-epoxypropyl)propyl trimethoxysilane in a weight ratio of 1:1:1.2, that is, 1.25 parts of γ-glycidyloxypropyl trimethoxysilane, 1.25 parts of 3-(3,4-epoxypropyl)propyl trimethoxysilane and 1.5 parts of 3-(2,3-epoxypropyl)propyl trimethoxysilane.
[0095] The carrier used for making the adhesive film is a carbon fiber woven cloth with a specification of 80 mesh and a surface density of 25g / m 2 .
[0096] A method for preparing the high-toughness and high-strength epoxy structural adhesive film comprises the following steps:
[0097] (1) Weigh 60 parts of bisphenol A diglycidyl ether epoxy resin, 20 parts of naphthyl epoxy resin, 20 parts of biphenyl novolac epoxy resin, 2.5 parts of 4,4'-diaminodiphenyl sulfone, 5 parts of 4,4'-diaminodiphenylmethane, 12.5 parts of dicyandiamide, 20 parts of polysulfone resin, 10 parts of phenolphthalein polyarylethersulfone, 10 parts of phenolphthalein polyaryletherketone, 5 parts of core-shell rubber, 5 parts of polymethacrylate glycidyl methacrylate, 1.25 parts of γ-glycidyloxypropyltrimethoxysilane, 1.25 parts of 3-(3,4-epoxypropyl)propyltrimethoxysilane, and 1.5 parts of 3-(2,3-epoxypropyl)propyltrimethoxysilane respectively by weight;
[0098] (2) Add 60 parts of bisphenol A diglycidyl ether epoxy resin, 20 parts of naphthyl epoxy resin and 20 parts of biphenyl phenolic epoxy resin weighed in step (1) into a reaction kettle, heat to 220° C., add 20 parts of polysulfone resin, 10 parts of phenolphthalein polyarylethersulfone and 10 parts of phenolphthalein polyaryletherketone at once under stirring, and keep the mixture at 200° C. for 85 minutes to obtain a homogeneous blended resin;
[0099] (3) using a kneader, uniformly mixing the homogeneous blended resin obtained in step (2) with 2.5 parts of 4,4'-diaminodiphenyl sulfone, 5 parts of 4,4'-diaminodiphenylmethane, 12.5 parts of dicyandiamide, 5 parts of core-shell rubber, 5 parts of poly(glycidyl methacrylate), 1.25 parts of γ-glycidyloxypropyltrimethoxysilane, 1.25 parts of 3-(3,4-epoxypropyl)propyltrimethoxysilane, and 1.5 parts of 3-(2,3-epoxypropyl)propyltrimethoxysilane to obtain a rubber material;
[0100] (4) hot-pressing the adhesive prepared in step (3) and the carbon fiber woven cloth to form a composite film to prepare an epoxy structural adhesive film;
[0101] The temperature of the hot pressing composite film forming is 90°C.
[0102] The high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is used for bonding aluminum alloy plates and for bonding continuous carbon fiber composite plates. The tensile shear strength is shown in Table 3:
[0103]
[0104] The impact strength of the high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is 61.5 kJ / m 2 .
[0105] The high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is used for bonding aluminum alloy plates at room temperature, and the peel strength is 6.28N / mm.
[0106] The glass transition temperature of the high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is 191.2°C.
[0107] Example 4
[0108] A high-toughness and high-strength epoxy structural adhesive film is prepared by preparing an adhesive material from epoxy resin, a curing agent, a thermoplastic resin, a functional toughening agent and a silane coupling agent in the following weight proportions, and then the adhesive material is compounded with a carrier for film manufacturing by hot pressing:
[0109] The rubber material includes 100 parts of epoxy resin, 25 parts of curing agent, 60 parts of thermoplastic resin, 30 parts of functional toughening agent and 5 parts of silane coupling agent;
[0110] The epoxy resin is composed of bisphenol A diglycidyl ether epoxy resin, naphthyl epoxy resin, and biphenyl phenolic epoxy resin in a weight ratio of 3:1:1, that is, 60 parts of bisphenol A diglycidyl ether epoxy resin, 20 parts of naphthyl epoxy resin, and 20 parts of biphenyl phenolic epoxy resin.
[0111] The curing agent is composed of 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenylmethane and dicyandiamide in a weight ratio of 1:1:3, namely, 5 parts of 4,4'-diaminodiphenyl sulfone, 5 parts of 4,4'-diaminodiphenylmethane and 15 parts of dicyandiamide.
[0112] The thermoplastic resin is composed of polysulfone resin, phenolphthalein polyarylethersulfone and phenolphthalein polyaryletherketone in a weight ratio of 1:0.75:0.25, namely 30 parts of polysulfone resin, 22.5 parts of phenolphthalein polyarylethersulfone and 7.5 parts of phenolphthalein polyaryletherketone.
[0113] The functional toughening agent is composed of core-shell rubber, epoxy-terminated nitrile rubber and poly(glycidyl methacrylate) in a weight ratio of 1:1:1, namely, 10 parts of core-shell rubber, 10 parts of epoxy-terminated nitrile rubber and 10 parts of poly(glycidyl methacrylate).
[0114] The epoxy-terminated nitrile rubber is prepared by mixing vinyl-terminated nitrile rubber, glycidyl methacrylate and an initiator in a molar ratio of 1:1.2:0.2 and reacting the mixture in an electric constant temperature forced air drying oven at 110°C through free radical polymerization for 65 minutes.
[0115] The chemical structure of the epoxy-terminated nitrile rubber is shown in Formula I:
[0116]
[0117] In the above structural formula, the value of n is 20, the value of m is 10, and the value of a is 15.
[0118] Poly(glycidyl methacrylate) is prepared by mixing glycidyl methacrylate and an initiator in a molar ratio of 1:0.2 and subjecting the mixture to copolymerization in an electric constant temperature blast drying oven at 110°C for 70 minutes.
[0119] The chemical structural formula of poly(glycidyl methacrylate) is shown in Formula II:
[0120]
[0121] The value of x in the above structural formula is 10.
[0122] The silane coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane, 3-(3,4-epoxypropyl)propyltrimethoxysilane and 3-(2,3-epoxypropyl)propyltrimethoxysilane in a weight ratio of 1.2:1:1, that is, 1.8 parts of γ-glycidyloxypropyltrimethoxysilane, 1.6 parts of 3-(3,4-epoxypropyl)propyltrimethoxysilane and 1.6 parts of 3-(2,3-epoxypropyl)propyltrimethoxysilane.
[0123] The carrier used for making the film is a glass fiber woven cloth with a specification of 80 mesh and a surface density of 25g / m 2 .
[0124] A method for preparing the high-toughness and high-strength epoxy structural adhesive film comprises the following steps:
[0125] (1) Weigh 60 parts of bisphenol A diglycidyl ether epoxy resin, 20 parts of naphthyl epoxy resin, 20 parts of biphenyl phenol formaldehyde epoxy resin, 5 parts of 4,4'-diaminodiphenyl sulfone, 5 parts of 4,4'-diaminodiphenylmethane, 15 parts of dicyandiamide, 30 parts of polysulfone resin, 22.5 parts of phenolphthalein polyarylethersulfone, 7.5 parts of phenolphthalein polyaryletherketone, 10 parts of core-shell rubber, 10 parts of epoxy-terminated nitrile rubber, 10 parts of polymethacrylate glycidyl methacrylate, 1.8 parts of γ-glycidyloxypropyltrimethoxysilane, 1.6 parts of 3-(3,4-epoxypropyl)propyltrimethoxysilane, and 1.6 parts of 3-(2,3-epoxypropyl)propyltrimethoxysilane respectively by weight;
[0126] (2) Add 60 parts of bisphenol A diglycidyl ether epoxy resin, 20 parts of naphthyl epoxy resin, and 20 parts of biphenyl phenolic epoxy resin weighed in step (1) into a reaction kettle, heat to 220° C., add 30 parts of polysulfone resin, 22.5 parts of phenolphthalein polyarylethersulfone, and 7.5 parts of phenolphthalein polyaryletherketone at once under stirring, and keep warm at 200° C. for 85 minutes to obtain a homogeneous blended resin;
[0127] (3) using a kneader, uniformly mixing the homogeneous blended resin obtained in step (2) with 5 parts of 4,4'-diaminodiphenyl sulfone, 5 parts of 4,4'-diaminodiphenylmethane, 15 parts of dicyandiamide, 10 parts of core-shell rubber, 10 parts of epoxy-terminated nitrile rubber, 10 parts of poly(glycidyl methacrylate), 1.8 parts of γ-glycidyloxypropyltrimethoxysilane, 1.6 parts of 3-(3,4-epoxypropyl)propyltrimethoxysilane, and 1.6 parts of 3-(2,3-epoxypropyl)propyltrimethoxysilane to obtain a rubber material;
[0128] (4) hot-pressing the adhesive prepared in step (3) and the glass fiber woven cloth to form a composite film to prepare an epoxy structural adhesive film;
[0129] The temperature of the hot pressing composite film forming is 90°C.
[0130] The high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is used for bonding aluminum alloy plates and for bonding continuous carbon fiber composite plates. The tensile shear strength is shown in Table 4:
[0131]
[0132] The impact strength of the high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is 60.7 kJ / m 2 .
[0133] The high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is used for bonding aluminum alloy plates at room temperature, and the peel strength is 6.21 N / mm.
[0134] The glass transition temperature of the high-toughness and high-strength epoxy structural adhesive prepared in this embodiment is 190.4°C.
[0135] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high-toughness and high-strength epoxy structural adhesive film, characterized in that: The high-toughness and high-strength epoxy structural adhesive film is made by hot-pressing a rubber compound and a carrier for film manufacturing; the rubber compound includes 75-100 parts of epoxy resin, 5-25 parts of curing agent, 20-60 parts of thermoplastic resin, 5-30 parts of functional toughening agent, and 3-5 parts of silane coupling agent, and the functional toughening agent includes a combination of one or two of terminal epoxy-butadiene nitrile rubber and poly(glycidyl methacrylate) and core-shell rubber; when the functional toughening agent includes terminal epoxy-butadiene nitrile rubber, poly(glycidyl methacrylate) and core-shell rubber, the weight ratio of the three is (1-2):(1-2):(1-5); when the functional toughening agent includes terminal epoxy-butadiene nitrile rubber / poly(glycidyl methacrylate) and core-shell rubber, the weight ratio of the two is (1-2):(1-5).
2. The high-toughness and high-strength epoxy structural adhesive film according to claim 1, characterized in that: The chemical structural formula of the epoxy-terminated nitrile rubber is shown in Formula I: In the above structural formula, the value range of n is 10 to 20, the value range of m is 5 to 10, and the value range of a is 10 to 15; The chemical structural formula of the poly(glycidyl methacrylate) is shown in Formula II: The value of x in the above structural formula ranges from 5 to 20.
3. The high-toughness and high-strength epoxy structural adhesive film according to claim 2, characterized in that: The epoxy-terminated nitrile rubber is prepared by mixing vinyl-terminated nitrile rubber, glycidyl methacrylate and an initiator in a molar ratio of 1:(1.05-1.2):0.2, and reacting the mixture in an electric constant temperature blast drying oven at 110±5°C through free radical polymerization for 60±5 minutes; the poly(glycidyl methacrylate) is prepared by mixing glycidyl methacrylate and an initiator in a molar ratio of 1:0.2, and reacting the mixture in an electric constant temperature blast drying oven at 110±5°C through copolymerization for 70±5 minutes.
4. The high-toughness and high-strength epoxy structural adhesive film according to claim 1, characterized in that: The epoxy resin is composed of bisphenol A diglycidyl ether epoxy resin, naphthyl epoxy resin and biphenyl phenol formaldehyde epoxy resin in a weight ratio of (1-4): (1-2): (1-2).
5. The high-toughness and high-strength epoxy structural adhesive film according to claim 1, characterized in that: The curing agent is composed of 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenylmethane and dicyandiamide in a weight ratio of (1-2):(1-2):(1-5).
6. The high-toughness and high-strength epoxy structural adhesive film according to claim 1, characterized in that: The thermoplastic resin includes any one or any several of polysulfone resin, phenolphthalein polyarylethersulfone, and phenolphthalein polyaryletherketone. When the thermoplastic resin is selected from polysulfone resin, phenolphthalein polyarylethersulfone, and phenolphthalein polyaryletherketone, the mass ratio of the three is 1:(0.25-1):(0.25-1); when the thermoplastic resin is selected from polysulfone resin and phenolphthalein polyarylethersulfone / phenolphthalein polyaryletherketone, the mass ratio of the two is 1:(0.25-1); when the thermoplastic resin is selected from phenolphthalein polyarylethersulfone and phenolphthalein polyaryletherketone, the mass ratio of the two is (0.25-1):(0.25-1).
7. The high-toughness and high-strength epoxy structural adhesive film according to claim 1, characterized in that: The silane coupling agent includes any one or more combinations of γ-glycidyloxypropyltrimethoxysilane, 3-(3,4-epoxypropyl)propyltrimethoxysilane, and 3-(2,3-epoxypropyl)propyltrimethoxysilane.
8. The high-toughness and high-strength epoxy structural adhesive film according to claim 1, characterized in that: The carrier for manufacturing the adhesive film includes one of non-woven fabric, carbon fiber woven fabric, polyester gauze, quartz fiber woven fabric or glass fiber woven fabric.
9. A method for preparing the high-toughness and high-strength epoxy structural adhesive film according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Add epoxy resin into a reaction kettle, heat to 200-220°C, add thermoplastic resin at one time under stirring, keep warm at 190-200°C for 80±5min, and prepare a homogeneous blended resin; Step 2: uniformly mixing the homogeneous blended resin with the functional toughening agent, the curing agent and the silane coupling agent by mechanical blending to obtain a rubber compound; Step 3: hot-press the prepared adhesive material and the carrier for film manufacturing to form a composite film, so as to obtain a high-toughness and high-strength epoxy structural adhesive film.
10. The preparation method according to claim 9, characterized in that: In step three, the hot pressing composite film forming temperature is 70-90°C.